Afro-descendants and indigenous people vulnerable to climate change: Disagreements about preventative measures of the Ecuadorian state - Victoria Salinas; William Cevallos; Karen Levy (Íconos)
The following article analyzes the situation of the province of Esmeraldas, located in the northeast of Ecuador and populated by afro-descendants and indigenous Chachi people. This province is one of the most affected by the high frequency and intensity of floods that cause innumerable material, economic and human loses. The objective of this research is to acknowledge the situation of the mentioned populations, identify their practices and representations, analyze how conditions of vulnerability related to the risks caused by floods are generated, and pinpoint the guides governmental institutions have used to develop their prevention and adaptation policies about this type of disas-ters. This study uses a qualitative methodology that is exploratory and descriptive in order to provide an account of the issue, showing that these populations recognize the level of vulnerability and risk in the area, but maintain their way of life because their actions respond to their own socio-cultural and economic constructions. In this sense, the conclusion of this study indicates that the preventative state measures, with relocation projects of the populations, are skewed, segmented, and authoritarian. The lack of communication, respect, and understanding for the forms of interaction of the community can be pinpointed as the reason for the failure of these initiatives.